Cardiovascular Complications of COVID-19 Vaccines - Liu, Runyu; Pan, Junbing; Zhang, Chunxiang; Sun, Xiaolei (Frontiers in Cardiovascular Medicine, 2022)
COVID-19 (Corona Virus Disease 19) has become a global public health catastrophe. Vaccination against SARS-CoV-2 is proven to be the most effective measure to suppress the pandemic. With the widespread application of the four vaccines, ChAdOx1, Ad26.COV2.S, BNT162b2 and mRNA-1273.2, several adverse effects have been reported. The most serious type of complication is cardiovascular related, including myocarditis, immune thrombocytopenia (ITP), cerebral sinus venous thrombosis, among others. All these adverse events undermine the health of the vaccinees and affect administration of the vaccines. As the distribution of COVID-19 vaccines is surrounded by suspicion and rumours, it is essential to provide the public with accurate reports from trusted experts and journals. Monitoring the safety of COVID-19 vaccines is an important and ongoing process that is also urgent. Thus, we summarize the cardiovascular complications of the major types of COVID-19 vaccines including mRNA vaccines which are now generally considered to be innovative vaccines and the future for vaccination against COVID-19, in addition to the underlying pathogenesis and potential therapeutics.